2017
DOI: 10.1103/physrevd.96.066008
|View full text |Cite
|
Sign up to set email alerts
|

Planck scale corrections to the harmonic oscillator, coherent, and squeezed states

Abstract: The Generalized Uncertainty Principle (GUP) is a modification of Heisenberg's Principle predicted by several theories of Quantum Gravity. It consists of a modified commutator between position and momentum. In this work we compute potentially observable effects that GUP implies for the harmonic oscillator, coherent and squeezed states in Quantum Mechanics. In particular, we rigorously analyze the GUP-perturbed harmonic oscillator Hamiltonian, defining new operators that act as ladder operators on the perturbed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 35 publications
3
56
0
Order By: Relevance
“…One usually assumes γ " 1{pM Pl cq, where M Pl is the Planck mass. Furthermore, the same parametrization was proved useful in perturbation theory [16]. Finally, notice that (1) represents an effective model giving rise to a minimal length of order " γ.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…One usually assumes γ " 1{pM Pl cq, where M Pl is the Planck mass. Furthermore, the same parametrization was proved useful in perturbation theory [16]. Finally, notice that (1) represents an effective model giving rise to a minimal length of order " γ.…”
Section: Introductionmentioning
confidence: 87%
“…The two formalism are in fact usually assumed to be equivalent. More specifically, when GUP is considered in the quantum domain, the usual tools of quantum mechanics are implemented, rooted in the Hamiltonian formalism (see, for example also [15][16][17]). On the other hand, for a description of classical systems or in quantum field theory, the machinery of the Lagrangian formalism is preferred (see, for example [18][19][20]).…”
Section: Introductionmentioning
confidence: 99%
“…We start our consideration with the simple premise that the modification of the fundamental commutator for a harmonic oscillator is equivalent to the nonlinear modification of the Hamiltonian by means of the perturbative transformation of momentum,p →p − β 0p 3 /(3M 2 p c 2 ), which restores the canonic commutator, [x,p] = i , at the expense of adding the non-linear term to the Hamiltonian of the resonator:Ĥ →Ĥ 0 + ∆Ĥ = p 2 /2m + mΩ 2 0x 2 /2 + β 0p 4 / 3m(M p c) 2 . Such non-linear correction results in the dependence of the oscillator resonance frequency on its energy [7,9,18]. The dynamics of the system can be described by a well known Duffing oscillator model characterized by amplitude dependence of the resonance frequency, i.e.…”
Section: Theorymentioning
confidence: 99%
“…It was in fact shown that the Generalized Uncertainty Principle (GUP) gives rise to small Planckscale dependent terms in non-relativistic and relativistic Hamiltonians. These terms can nevertheless have potential experimental implications [1][2][3]. In particular, it was shown that there were p 3 and p 4 (p " momentum, q " position) Planck-scale corrections to the quantum Harmonic Oscillator (HO).…”
Section: Introductionmentioning
confidence: 99%
“…Such terms affect energy eigenvalues and eigenstates, that can be studied using standard perturbation techniques [4]. In a recent paper [3], it was shown however that an alternative approach can be pursued. Specifically, raising and lowering (or ladder) operators for the perturbed HO can be defined directly.…”
Section: Introductionmentioning
confidence: 99%